A Construction of a Mathematical Literacy Diagnostic Test for 9th Grade Students in Chiang Mai Province - Jailar, Adirek; Intanate, Nampueng (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
This study sought to investigate the current state of deficiencies in mathematical literacy and to construct a specific diagnostic test for 9th grade students in Chiang Mai Province. This study was conducted in two phases. In Phase 1, the researchers conducted a PISA-based survey to identify literacy gaps. The instrument focuses on three core mathematical problem-solving processes: formulating mathematical situations, employing mathematical concepts and procedures for solutions, and interpreting and evaluating mathematical outcomes. The preliminary test was administered to a sample of 385 students via stratified random sampling. The deficiencies of 22 specific areas were revealed from 10 identified behavioral indicators. Phase 2, a four-tier mathematical literacy diagnostic test, consisted of four distinct sections: the first tier is the student's answer; the second tier is confidence in that answer; the third tier is the reasons for the answers; and the fourth tier is confidence in the reasoning provided. This diagnostic test was implemented with a sample group of 100 students. Three versions were developed: Version 1 (Formulating, 15 items), Version 2 (Employing, 20 items), and Version 3 (Interpreting, 15 items). All the test items showed difficulty indices ranging from 0.21 to 0.79 and discrimination indices between 0.20 and 0.72, respectively. In addition, all versions revealed high reliability coefficients of .86, .89, and .78, respectively, and concurrent validity coefficients were established at .82, .82, and .83, respectively.